Assessing the Affordability of Nutrient-Adequate Diets - Schneider, Kate (World Bank, Washington, DC, 2021)
The affordability of nutritious diets is increasingly used as a metric of how well a food system provides access to nutritious diets for all. Recent work on least-cost diets has focused on individuals, while most food and anti-poverty programs and policies target the household level. Members within households have differing nutritional needs, presenting the methodological question: how should the cost of nutritious diets be estimated at the household level This study develops bounds on the cost, affordability, and seasonal variation of least-cost diets for whole households, illustrated with the example of Malawi. When intrahousehold sharing is not possible to observe, the bounded approach provides insights into the range of the cost and affordability, and the extent to which the cost may vary seasonally. The results reveal that when meals are shared, ignoring demographic diversity within households greatly underestimates the affordability of adequate diets.